The concept and estimation of direct, indirect and "total" currency substitution in money demand - Natividad, Fidelina B. (1989)
This paper reviews briefly the literature on currency substitution and presents two alternative specifications of money demand function which take into account different forms of currency substitution. It demonstrates that the money demand function which separates direct currency substitution from indirect currency substitution is mathematically equivalent to one that combines the two effects.
Keywords: Currency substitution; Demand for money